PEMBERIAN JENIS LIMBAH KULIT BUAH KAKAO DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) - Hutabarat, Joni Balutan Apriadi; Yoseva, Sri; ', Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is determining the effect of some kinds from cocoa’s kind waste and NPK fertilizer and to get the best dose for the growth of cocoa plantation. This research was conducted in the experimental field and Laboratory of Production Faculty of Agriculture, University of Riau in Campus Binawidya Km 12.5 Simpang Baru Pekanbaru. This research was conducted from January to April 2015. The research used Completely Randomized Design factorial that consisting of two factors. The first factor is the cocoa’s kind waste (T) consists of four levels, they are T1 = wet waste in chopped 100 g/plant; T2 = dry waste chopped 100 g/plant; T3 = dry waste burned 100 g/plant; T4 = compost cocoa exocarpium waste 100 g/plant. The second factor is the NPK fertilizer (U), which consists of 4 levels, namely U (3.75, 7.5, 11:25, 15) g/polybag. Both these factors resulted in 16 treatsment combinations, each combination made three replications, so that there are 48 experimental units. Each experimental unit consisted of four plants, so the total crop was 192 plants. Parameters measured were seedling height, number of leaves, stem diameter, leaf area, the ratio of crown roots and seedling dry weight. Data obtained from the research results were statistically analyzed by analysis of variance followed by a further test of Duncan's New Multiple Range Test (DNMRT) at 5%. Based on the research the provision of cocoa’s kind waste and NPK fertilizer on the cocoa seeds that have been made, the result showed that the treatment cocoa’s kind waste and NPK fertilizer had no significant on all parameters of observation. Treatment of cocoa’s kind waste burnt 100 g/seed and fertilizer NPK 7.5 g/seeds can be recommended to get the growth of cocoa’s seedling. Keywords : cocoa, cocoa’s kind waste and NPK fertilizer